Imagery, imagination, and narratives: Draft for a theory of image - De Morais, Osvando José [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2020)
Through this study, we reflect on images of the 21st century and analyze them based on Ítalo Calvino’s proposals for this century that is understood by him in the 1980s as six elements of grandeur or qualities essential to narratives in their various senses but fundamental to understanding the audiovisual aspect of today’s “media.” We discuss and analyze these specific characteristics in the Italian author’s works, and through the concepts of image, imagination, and imaginary by Jean-Paul Sartre, we focus on a special dimension that is already methodologically constituted as theoretical research. This results in forming a solid and fundamental basis for constructing and creating narratives applied to images that carry stories and are adaptable to any medium. Through the study results, it is deduced that the concept of image as the awareness of some experience, the central object of Sartre’s reflections, converses with and philosophically completes Calvino’s narrative and literary greatness. Finally, we find that the theories and concepts by Calvino and Sartre broadly subsidize studies applied to producing and creating literary narrative texts and technical instrumental scripts, intermediaries to narratives with independent supporting images.
El imaginario, imaginación y narrativas: Esbozo para una teoría de las imágenes
O imaginário, imaginação e narrativas: Esboço para uma teoria das imagens
Keywords: Images; Italo Calvino; Jean-Paul Sartre; Literature; Narratives; Scripts